2010
DOI: 10.1097/nan.0b013e3181f85a73
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of the Phlebitis and Infiltration Scales for the Assessment of Complications of Peripheral Vascular Access Devices

Abstract: To prevent complications from peripheral vascular access device (PVAD) therapy, the Infusion Nurses Society (INS) developed 2 scales to measure the extent and severity of phlebitis and infiltration in PVADs. This study evaluated the psychometric properties of these scales to validate them with respect to their interrater reliability, concurrent validity, feasibility, and acceptability. A total of 182 patients at 2 sites were enrolled, and 416 observations of PVAD sites were made. Two nurses independently rated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 7 publications
0
36
1
5
Order By: Relevance
“…İntravenöz sıvının yerleşim yerinden ayrılması, tespit altından sızıntı olması da infiltrasyon bulguları arasındadır. Ancak bazı durumlarda komplikasyonlar daha fazla olabilir, deride kabarıklık, solukluk, kapiller dolum zamanında uzama ve dokuda nekroz görülebilir (4)(5)(6).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…İntravenöz sıvının yerleşim yerinden ayrılması, tespit altından sızıntı olması da infiltrasyon bulguları arasındadır. Ancak bazı durumlarda komplikasyonlar daha fazla olabilir, deride kabarıklık, solukluk, kapiller dolum zamanında uzama ve dokuda nekroz görülebilir (4)(5)(6).…”
Section: Introductionunclassified
“…Bunlar genel olarak; ağrı, renk değişikliği, solukluk, şeffaflık, ödem, sızıntı gibi çok önemli göstergelerdir (6,15,16). Çalışmamızda da bu parametreler yer almaktadır.…”
unclassified
“…The scale is a valid and reliable tool 22 that facilitates tracking of the sequelae of infusions and provides ongoing monitoring of phlebitis. Documentation of a catheter's location and reasons for discontinuing a catheter are also required.…”
Section: Analysis Of Maximum Likelihood Estimatesmentioning
confidence: 99%
“…It was found that the scale was easy to administer, with rapid implementation (mean of 1.3 minutes), and was clinically appropriate. (14) The authors also indicated the need to make other psychometric studies to assess the validity and reliability of the scale.…”
Section: Introductionmentioning
confidence: 99%